Isolation and Characterization of Secondary Metabolites from Arctic Marine Hydroids - Harvey, Therese (UiT Norges arktiske universitet, 2018)
Marine bioprospecting is the systematic search for and discovery of products from Nature, with potential of being developed into commercially available pharmaceuticals. The ocean represents the largest habitat on Earth, and represent a great resource of organisms with unique biological and chemical diversity. The marine environment makes the living condition challenging. To survive these conditions, marine organisms produce numerous potent secondary metabolites to avoid predation and invasion by pathogenic microorganisms. Due to their natural function and chemical diversity, secondary metabolites are believed to have enormous potential as lead compounds in development of commercial products. The aim of this thesis was to isolate and characterize halogenated secondary metabolites from organic extracts of Arctic marine Hydroids. The crude organic extracts were analyzed by using UHPLC-HR-MS, to evaluate the presence of known and already reported compounds. Based on the data from the HR-MS analysis, three brominated compounds believed to be novel were selected for isolation. Chemistry-guided isolation was conducted for the selected compounds using mass guided preparative HPLC. During the isolation process, two other compounds were selected for isolation for the reason that they appeared to be present in abundant amount and that seems easy to isolate, in addition to the preselected compounds. At the end, one compound was isolated in amounts allowing structure elucidation using NMR, and turned out to be the known compound Loliolide. Loliolide was first isolated from Lolium perenne in 1964, but this is the first time that this compound has been isolated from Hydroids. The compound was screened for antibacterial activity and inhibition of biofilm formation, but no bioactivity was found. The result form this thesis shows that isolation of a high enough amount of secondary metabolites for structure elucidation and bioactivity screening can be a challenge due to difficulty of collecting enough biomass. The results also ...